Oral-Motor Function in Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The communication skills, oral-motor function and respiration patterns of 20 girls with Rett syndrome were studied at the Crippled Childrens Division, Oregon Health Sciences University, Portland, OR.